2010
DOI: 10.1016/j.jjcc.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapeutic option for refractory heart failure in elderly patients with chronic kidney disease by incremental peritoneal dialysis

Abstract: Incremental PD could represent a novel therapeutic option for elderly patients with refractory HF. In addition to fluid removal by PD, correction of renal anemia, preservation of kidney function, and avoidance of high-dose diuretic therapy may play a role in maximizing clinical benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 22 publications
7
58
0
6
Order By: Relevance
“…In many of the other studies that examined the effect of PUF on GFR, PUF was found to be ineffective on GFR (42,56,68,79). In a meta-analysis including six studies with a total of 282 patients without indications of renal replacement therapy, there was no significant difference in GFR before and after PUF (80).…”
Section: How Does Peritoneal Dialysis Affect Glomerular Filtration Rate?mentioning
confidence: 98%
See 2 more Smart Citations
“…In many of the other studies that examined the effect of PUF on GFR, PUF was found to be ineffective on GFR (42,56,68,79). In a meta-analysis including six studies with a total of 282 patients without indications of renal replacement therapy, there was no significant difference in GFR before and after PUF (80).…”
Section: How Does Peritoneal Dialysis Affect Glomerular Filtration Rate?mentioning
confidence: 98%
“…The peritoneal dialysis does not introduce this vicious cycle because it removes the excess fluid from the body continuously and in a slow manner (41). However, there are no abrupt changes in renal hemodynamics with UF which is made slowly and controlled by PD and, by this way, PD has superiority to diuretics by preserving residual renal function (42).…”
Section: Why Peritoneal Dialysis Is Chosen In the Treatment Of Heart mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, they are uncontrolled and the groups studied are small. Patients with coexisting renal failure may be treated with intermittent PD [21], continuous ambulatory PD [22][23][24][25][26] or automated PD [27][28][29][30], while in those without significant impairment of renal function -a single nightly exchange (PUF) with osmotic agent (optimally icodextrin) is sufficient [31][32][33][34][35]. In the vast majority of cases PD/PUF was performed in patients with advanced CHF and symptoms of cardiorenal syndrome as an addition to standard therapy.…”
Section: Peritoneal Ultrafiltrationmentioning
confidence: 99%
“…It usually concerned elderly patients with numerous comorbidities and various degrees of renal impairment, disqualified from heart transplantation and refractory to pharmacological treatment. In some centers, extracorporeal UF was initially performed for quick reduction of fluid overload [28,29,[32][33][34][35], while in the others therapy was commenced with PUF or PD. PUF/PD dose was matched to individual patient's needs in order to obtain optimal UF on one hand, while achieving adequate balancing of metabolic disturbances associated with renal impairment on the other.…”
Section: Peritoneal Ultrafiltrationmentioning
confidence: 99%